PRELIMINARY SIMULATION OF EGG AND LARVAL DISPERSAL OF CORAL REEF FISH IN NHA TRANG MARINE PROTECTED AREA - Viet, Dang Do Hung; Vinh, Vu Duy; Chien, Pham Van; The, Nguyen Duc (Vietnam Journal of Marine Science and Technology, 2014)
Modeling the dispersal of coral reef fish eggs and larvae (FE-FL) in Nha Trang bay MPA simulated two scenarios in 03/2009 and 08/2009. The assumption each time for scenario was 30 days. The dispersal results of FE-FL from the Nha Trang bay to the surrounding areas just concentrated in coastal areas with very small quantities. A small number of FE-FL under the effects of water current were also take to the Northern coastal areas and the Southern coastal areas but no FE-FL spread to open sea. The dispersal range was not much different between the tidal phases and monsoons but significantly affected by the source (fish eggs produced).